Progress of research on graphene and its derivatives in bone and cartilage repair - Yu, Shilong; You, Mingke; Zhou, Kai; Li, Jian (Frontiers in Bioengineering and Biotechnology, 2023)
In recent years, graphene and its derivatives have gained wide attention in the biomedical field due to their good physicochemical properties, biocompatibility, and bioactivity. Its good antibacterial, osteoinductive and drug-carrying properties make it a promising application in the field of orthopedic biomaterials. This paper introduces the research progress of graphene and its derivatives in bone tissue engineering and cartilage tissue engineering and presents an outlook on the future development of graphene-based materials in orthopedics.